Time Course of Growth and Protease Production by Spoilage Bacteria Under Different Culture Conditions - Philip, Rosamma; P., Lakshmana Perumalsamy (Fishery Technology, 2025)
Four strains of proteolytic bacteria which were assessed as potential fish spoilers were used for the study. They were Pseudomonas sp. Ca 173 isolated from Penaeus indicus, Pseudomonas sp. Ca 386 from Metapemeus dobsoni, Vibrio sp. Ca 377 from Liza parsia and Vibrio sp. Ca 761 from Penaeus indicus. The influence of pH, temperature and sodium chloride concentrations on the growth and protease production of these bacterial isolates were studied. The study shows that the requirements of the normal flora of fish and prawns for maximum protease production are 30PC, neutral pH (7) and absence of NaCl. Moreover, the protease production was observed at late logarithmic or early stationary phase. This suggests that the inhibition of the bacterial growth in the late logarithmic or early stationary phase will arrest the bacterial fish spoilage to some extent.